2016
DOI: 10.1177/2167479515588760
|View full text |Cite
|
Sign up to set email alerts
|

Permanently Desiring the Temporary? Snapchat, Social Media, and the Shifting Motivations of Sports Fans

Abstract: The social media application Snapchat has ascended rapidly, quickly becoming the third most utilized platform of millennials with a valuation as high as US$19 billion. A national survey of 125 respondents revealed that people using Snapchat to follow sports devote roughly the same amount of time to the platform as Facebook and more time than Twitter, Instagram, or Pinterest. Despite finding other platforms better for sport information seeking, relaxation, and interaction, respondents still reported using Snapc… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

1
68
3
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 65 publications
(73 citation statements)
references
References 29 publications
1
68
3
1
Order By: Relevance
“…In the context of sport, Filo et al (2015, p.167) define social media as "..new media technologies facilitating interactivity and co-creation that allow for the development and sharing of user-generated content among and between organizations…and individuals". Social media can be used during live sporting telecasts, enabling comments to be posted and exchanged with others online (Billings et al, 2017). This represents an interesting viewing scenario where the activity of watching television (TV) is augmented with the dynamic interactive communication capabilities of social media (Filo et al, 2015;Lim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…In the context of sport, Filo et al (2015, p.167) define social media as "..new media technologies facilitating interactivity and co-creation that allow for the development and sharing of user-generated content among and between organizations…and individuals". Social media can be used during live sporting telecasts, enabling comments to be posted and exchanged with others online (Billings et al, 2017). This represents an interesting viewing scenario where the activity of watching television (TV) is augmented with the dynamic interactive communication capabilities of social media (Filo et al, 2015;Lim et al, 2015).…”
Section: Introductionmentioning
confidence: 99%
“…One study, for example, visualized the spatiotemporal distribution of snaps in three US cities (Juhász & Hochmair, 2018). Other papers have examined the reasons that motivate users to share snaps (Habib, Shah & Vaish, 2019), and have explored the time spent snapping compared to other social media platforms (Billings, Qiao, Conlin & Nie, 2017). The research presented here extends the literature by identifying socio-economic factors associated with the use of three popular social media platforms, and by providing a spatial and temporal description of Snapchat activity patterns.…”
Section: Introductionmentioning
confidence: 88%
“…The results displayed that, although differences were existed between them, people also achieved their social connection in Facebook online ecosystem and was able to fulfill their desired emotional goals. As for Snapchat, it has become the third most used millennial-generation platform, with a valuation of 19 billion US dollars (Billings et al, 2015). Billings et al (2015) conducted a study on viewer's attention to sports through Snapchat.…”
Section: Sports and Social Mediamentioning
confidence: 99%
“…As for Snapchat, it has become the third most used millennial-generation platform, with a valuation of 19 billion US dollars (Billings et al, 2015). Billings et al (2015) conducted a study on viewer's attention to sports through Snapchat. The result of a national survey of 125 respondents showed that the time people spent on Snapchat is almost as much as they did on Facebook, but both are less than they did on Twitter, Instagram, or Pinterest.…”
Section: Sports and Social Mediamentioning
confidence: 99%